2007
DOI: 10.1111/j.1365-2710.2007.00826.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of l-phenylalanine supplementation and a high-protein diet on pharmacokinetics of cefdinir in healthy volunteers: an exploratory study

Abstract: In humans, L-phenylalanine supplementation and HPD do not seem to upregulate intestinal and renal oligopeptide transport in the ranges of duration and dose examined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…In the paper by Fujita et al (2007) it is shown that phenylalanine supplementation (2.5 g, three times a day for 12 days in healthy volunteers) did not seem to upregulate intestinal oligopeptide transport. The substance used was cefdinir, a β-lactam antibiotic with a normally low absorption (33%).…”
Section: Metabolism -Gastrointestinal Uptakementioning
confidence: 98%
See 1 more Smart Citation
“…In the paper by Fujita et al (2007) it is shown that phenylalanine supplementation (2.5 g, three times a day for 12 days in healthy volunteers) did not seem to upregulate intestinal oligopeptide transport. The substance used was cefdinir, a β-lactam antibiotic with a normally low absorption (33%).…”
Section: Metabolism -Gastrointestinal Uptakementioning
confidence: 98%
“…High levels of specific amino acids can also affect transporters and protein synthesis. The literature search for publications since 2002 relating to this area identified two articles that have been evaluated (Ferland et al 2007;Fujita et al 2007).…”
Section: Effects Of Aspartame On Metabolism Of Endogenous and Exogenomentioning
confidence: 99%
“…Chen et al [ 6 ] introduced a sensitive LC-MS/MS method for cefdinir determination in human plasma, which needed high requirement of instruments and bear high-cost. Fujita et al [ 7 ] reported a modifi ed HPLC method for pharmacokinetic study using solid-phase A simple and sensitive HPLC method was developed to determine cefdinir (CAS 91832-40-5) in human plasma. The method was validated by investigating the accuracy and precision for intraand inter-day runs in a linear concentration from 0.05-2.0 μg/ml.…”
Section: Introduction ▼mentioning
confidence: 99%